2018
DOI: 10.1002/jcb.26528
|View full text |Cite
|
Sign up to set email alerts
|

Nanos2 promotes differentiation of chicken (Gallus gallus) embryonic stem cells to male germ cells

Abstract: Nanos2 is an evolutionarily conserved RNA-binding protein containing 2 CCHC-type zinc finger motives. Here, we report that Nanos2 is strongly expressed in the testis compared to other tissues in chicken (Gallus gallus). Overexpression and knockout plasmid vectors were constructed, and in-vitro Cas9/gRNA digestion and T7 endonuclease I (T7E1) assay indicated that Nanos2-g1 possessed the highest knockout activity. In vitro and in vivo, Nanos2 overexpression accelerated the production of embryoid bodies (EBs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…By injecting sea urchin with nanos2 dsRNA, we successfully reduced the expression of not just our target gene, but also other conserved germ cell marker genes like boule (Figure 7). In vertebrates as well as invertebrates, nanos2 and boule have been identified as germ cell markers and play important roles in germ cell development [12,35]. The decreased expression of germ cell marker genes ( nanos2 and boule ) indicated that the number of germ cells may have decreased, and that Mnnanos2 is essential for germ cell survival in adult sea urchin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By injecting sea urchin with nanos2 dsRNA, we successfully reduced the expression of not just our target gene, but also other conserved germ cell marker genes like boule (Figure 7). In vertebrates as well as invertebrates, nanos2 and boule have been identified as germ cell markers and play important roles in germ cell development [12,35]. The decreased expression of germ cell marker genes ( nanos2 and boule ) indicated that the number of germ cells may have decreased, and that Mnnanos2 is essential for germ cell survival in adult sea urchin.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Nanos2 is predominantly detected in male germ cells in Mammalia (e.g., mouse), and knockout of Nanos2 leads to a complete loss of spermatogonia [8,10,11]. In Aves (e.g., chicken), nanos2 is mainly expressed in testes and promotes the transformation of embryonic stem cells into male germ cells [12]. In contrast, the expression pattern of nanos2 in fish shows non-uniformly species-specific characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Culture. ESCs were isolated from freshly fertilized eggs as previously described [10,11]. ESCs were induced by medium containing 10 -5 mol/L RA, and viruses were added with a titer of 5 × 10 8 TU/mL on D0 induction.…”
Section: Esc Isolation and Inductionmentioning
confidence: 99%
“…The embryonic genital ridges were collected at 4.5 days, and testes separated at 18.5 days after incubation for RNA, Periodic Acid-Schiff stain (PAS), FCM, Western blot and other tests. [10].…”
Section: Embryo Injection Experimentmentioning
confidence: 99%
“…It has been reported that Nanos2 is involved in the formation of spermatids and meiosis that can inhibit the expression of the meiosis initiation gene Stra8 (Yao et al, 2014;Zeng et al, 2013). Our previous study found that overexpression of Nanos2 in vitro can promote the production of PGCs and SSCs, while knockout of Nanos2 can result in the inhibition of gonadal development and thus inhibit the production of male germ cells (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 98%